STUDY ON DOPING EFFECTS OF PORPHYRIN DERIVATES ON EMERALDINE SALT OF POLYANILINE AND ITS APPLICATION IN DYE-SENSITIZED SOLAR CELLS - NURHAYATI (NIM : 20513031), NUNIK
Since the discovery of conductive polymers in the mid-1970s, research and industry on conductive polymers are growing. Emeraldine salt of polyaniline (PANI-ES) is one of the conductive polymers that commonly used in electronic devices. Co-doping PANI-ES with a variety of compounds has been reported, including the conjugated-electron-rich compounds. Porphyrin is a conjugated electron-rich molecule; however, co-doping PANI-ES with porphyrin has not been reported yet. Porphyrin compound is an organic semiconductor which can be applied as optoelectronic devices, such as solar cells, sensors, LEDs, detectors, lasers, and others. The purpose of this study is to observe the doping effects of porphyrin derivates on PAN-ES that applied on DSSC device as counter electrode. Several variations of doping were carried out in this study, including variation on concentration of TPP/PANI-ES, types of porphyrin, and temperature. Conductivity measurements at variation on concentration of TPP/PANI-ES show the nature of metallic and semiconductor. Various types of porphyrins give the same effects on PANI-ES conductivity, which are metallic and semiconductor, except for 3-TMPP doped PANI-ES, where it shows only semiconductor behaviour. On the heat treatment at various temperature, deprotonation and oxidation occured on both PANI-ES and TPP/PANI-ES due to the heating. This can be observed from Raman shift, where C=N mode of quinonoid ring shifts from 1500 cm-1 to 1487-1488 cm-1 and from 1479 cm-1 to 1491-1498 cm-1 for PANI-ES and TPP/PANI-ES, respectively. Deprotonation and oxidation are also confirmed at another vibration mode, namely vC-C mode of semiquinonoid ring which transforms to vC = C mode of quinonoid ring from 1596-1602 cm-1 to 1585-1587 cm-1 and from 1596-1597 cm-1 to 1585-1586 cm-1 for PANI-ES and TPP/PANI-ES, respectively. Heat treated PANI-ES and TPP/PANI-ES have optimum condition at 120oC , where they show the maximum conductivity. As the counter electrode in a DSSC device, they can enhance efficiency of DSSC from 0.62% to 0.78% for PANI-ES and 1.22% in case of TPP/PANI-ES.